2017
DOI: 10.1167/iovs.17-22257
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Corneal Nerve Fiber Density in Type 2 Diabetes by Wide-Area Mosaic Analysis

Abstract: Citation: Lagali NS, Allgeier S, Guimarães P, et al. Reduced corneal nerve fiber density in type 2 diabetes by wide-area mosaic analysis. Invest Ophthalmol Vis Sci. 2017;58:6318-6327. DOI:10.1167/iovs.17-22257 PURPOSE. To determine if corneal subbasal nerve plexus (SBP) parameters derived from widearea depth-corrected mosaic images are associated with type 2 diabetes. METHODS.One hundred sixty-three mosaics were produced from eyes of 82 subjects by laserscanning in vivo confocal microscopy (IVCM). Subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 38 publications
3
46
1
Order By: Relevance
“…29 The diagnostic ability of IVCCM may be further enhanced by assessing the inferior whorl or using wide-area mosaics, which take into account both proximal and distal corneal nerve morphology. 30,31 Multiple pathogenetic mechanisms, including advanced glycation, increased flux through the sorbitol pathway, and oxidative stress, have been implicated in the development of diabetic neuropathy. 32 Experimental studies using a combination of menhaden oil, a-lipoic acid, and enalapril have been shown to ameliorate oxidative and inflammatory stress and improve distal corneal nerve morphology.…”
Section: Discussionmentioning
confidence: 99%
“…29 The diagnostic ability of IVCCM may be further enhanced by assessing the inferior whorl or using wide-area mosaics, which take into account both proximal and distal corneal nerve morphology. 30,31 Multiple pathogenetic mechanisms, including advanced glycation, increased flux through the sorbitol pathway, and oxidative stress, have been implicated in the development of diabetic neuropathy. 32 Experimental studies using a combination of menhaden oil, a-lipoic acid, and enalapril have been shown to ameliorate oxidative and inflammatory stress and improve distal corneal nerve morphology.…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of this study in 2014, previous participants were invited as part of a 10 year follow-up. Details of the subject recruitment including inclusion and exclusion criteria and study flowchart are given elsewhere 30 . Subjects did not have active corneal disease or inflammation, and were not taking any topical ocular medications at the time of examination.…”
Section: Methodsmentioning
confidence: 99%
“…Those with diagnosed diabetes were further sub-grouped into short duration (diagnosis <10 years prior to ophthalmic examination, 11 individuals) and long duration (≥10 years since diagnosis, 28 individuals). Subgroupings were based on the oral glucose tolerance test (OGTT) and the clinical diagnosis of type 2 diabetes mellitus, with details given elsewhere 30 . The study subjects were all residents in the same county, located in the northern part of Sweden.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A full description of the cohort of subjects with inclusion and exclusion criteria has been given elsewhere 33 . Subjects were examined based on an initial cohort of 129 age- and sex-matched subjects aged 60±1 years at initial inclusion in 2004 (ref.…”
Section: Methodsmentioning
confidence: 99%